Auxetic materials : general concepts - Steffens, F. (2013)
Auxetic materials are different from other conventional materials since they present a negative Poisson’s ratio. These materials present an unusual behavior: when stretched (elongated in the longitudinal direction), their cross-section is increased. The multidisciplinary application is the great feature of these new materials, which can be used in various areas, including: medicine, architecture, civil engineering, sport clothing, high-performance equipment, protection against explosives, insulation, filters among others. However, its applicability may be even more exploited. This paper presents a scientific review of auxetic fibrous materials, considering their operating mechanisms, their different representations, manufacturing techniques, examples of applications and, mainly, to explore the scientific importance of these new materials in the development of special products for the textile industry.